Chemical solution and method for producing chemical solution

A chemical solution with controlled metal nanoparticle sizes and a multistage filtration process effectively addresses defects in EUV exposure, enhancing defect suppression and resist pattern formation in semiconductor manufacturing.

JP2024174017AActive Publication Date: 2024-12-13FUJIFILM CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024165958
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-01-12
Filing Date
2024-09-25
Publication Date
2024-12-13
Estimated Expiration
2039-01-07

AI Technical Summary

Technical Problem

Chemical solutions used in semiconductor manufacturing processes, particularly for EUV exposure, suffer from defects during resist pattern formation, which conventional methods fail to adequately address.

Method used

A chemical solution containing metal-containing particles with a specific size distribution and composition, including metal nanoparticles of 0.5 to 17 nm, is formulated with controlled ratios and combined with a multistage filtration process to achieve defect suppression.

Benefits of technology

The solution provides excellent defect suppression performance during EUV exposure, ensuring finer resist patterns and reduced defects in semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174017000001_ABST
    Figure 2024174017000001_ABST
Patent Text Reader

Abstract

To provide chemical solution that has excellent defect suppression performance even when applied to a resist process by EUV exposure, and to provide a method for producing chemical solution.SOLUTION: Chemical solution of the present invention is chemical solution containing an organic solvent and a metal-containing particle that contains metal atom, and in which, of the metal-containing particles, the number of contained particles of metal nanoparticle having particle size of 0.5 to 17 nm per unit volume of chemical solution is 1.0×101 to 1.0×109 particles / cm3.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a chemical solution and a method for producing the chemical solution. [Background technology]

[0002] When manufacturing semiconductor devices through wiring formation processes including photolithography, chemical solutions containing water and / or organic solvents are used as pre-wet solutions, resist solutions (resist compositions), developing solutions, rinsing solutions, stripping solutions, chemical mechanical polishing (CMP) slurries, and post-CMP cleaning solutions, or as diluting solutions thereof. In recent years, advances in photolithography technology have led to the advancement of finer patterns. One method for achieving finer patterns is to use shorter wavelength exposure light sources, and attempts are being made to form patterns using EUV (extreme ultraviolet) and other light sources with shorter wavelengths instead of conventionally used ultraviolet light, KrF excimer lasers, and ArF excimer lasers. The development of pattern formation using the above-mentioned EUV or the like is proceeding with a target resist pattern width of 10 to 15 nm, and the above-mentioned chemicals used in this process are required to have even greater defect suppression performance.

[0003] As a method for producing a chemical solution used in conventional resist pattern formation, Patent Document 1 describes a method for producing a resist composition used in a semiconductor device manufacturing process, in which a manufacturing device for the resist composition is washed with a cleaning solution, the cleaning solution is removed from the manufacturing device and spin-coated onto an evaluation substrate, and the change in defect density for defects of 100 nm or more before and after coating on the evaluation substrate is 0.2 defects / cm 2 and then producing a resist composition in a production apparatus." and the above document states that when a chemical solution (resist composition) produced by this method was used for ArF exposure, pattern defects and the like were suppressed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-049395 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present inventors have found that when a pattern is formed by EUV exposure using a resist composition containing a chemical solution produced by the above-mentioned production method, defects occur. Therefore, an object of the present invention is to provide a chemical solution that is less likely to cause defects even when applied to a resist process using EUV exposure, in other words, that has excellent defect suppression performance even when applied to a resist process using EUV exposure. Another object of the present invention is to provide a method for producing a chemical solution. [Means for solving the problem]

[0006] As a result of intensive research into solving the above problems, the present inventors have found that the above problems can be solved by the following configuration.

[0007] [1] A chemical solution containing an organic solvent and metal-containing particles containing metal atoms, wherein the metal-containing particles are metal nanoparticles having a particle diameter of 0.5 to 17 nm, and the particle number per unit volume of the chemical solution is 1.0 × 10 1 ~1.0×10 9 pieces / cm 3 That is, liquid medicine. [2] The drug solution described in [1], wherein the particle size distribution based on the number of metal-containing particles has a maximum value in at least one range selected from the group consisting of a particle size range of less than 5 nm and a particle size range of more than 17 nm. [3] The drug solution according to [2], wherein the particle size distribution has a maximum value in the particle size range of 0.5 nm or more and less than 5 nm. [4] The chemical solution according to any one of [1] to [3], which is used in the manufacture of a semiconductor device. [5] The chemical solution according to any one of [1] to [4], wherein the metal nanoparticles are at least one type selected from the group consisting of particles A consisting of simple metal atoms, particles B consisting of an oxide of a metal atom, and particles C consisting of simple metal atoms and an oxide of a metal atom. [6] The drug solution described in [5], in which the ratio of the number of particles A contained per unit volume of the drug solution to the total number of particles B contained and the number of particles C contained per unit volume of the drug solution is less than 1.0. [7] Particle number ratio is 1.0×10 -1 The drug solution described in [5] or [6] below. [8] The chemical solution according to any one of [1] to [7], further comprising an organic compound having a boiling point of 300° C. or higher. [9] The chemical solution according to [8], wherein at least a portion of the metal nanoparticles are particles U that contain an organic compound.

[10] At least a portion of the metal nanoparticles are particles U containing an organic compound and particles V not containing an organic compound, and the ratio of the number of particles U to the number of particles V per unit volume of the drug solution is 1.0 × 10 1 The above-mentioned medicinal solution described in [8] or [9].

[11] The chemical solution according to any one of [1] to

[10] , wherein the metal nanoparticles contain at least one type selected from the group consisting of metal nanoparticles containing Pb atoms and metal nanoparticles containing Ti atoms.

[12] The chemical solution according to any one of [1] to

[11] , wherein the metal nanoparticles contain metal nanoparticles containing Pb atoms and metal nanoparticles containing Ti atoms.

[13] The ratio of the number of metallic nanoparticles containing Pb atoms to the number of metallic nanoparticles containing Ti atoms per unit volume of the drug solution is 1.0 × 10 -3 The drug solution according to any one of [1] to

[12] , wherein the molecular weight is 0.01 to 0.25.

[14] A method for producing the chemical solution according to any one of [1] to

[13] , comprising a filtration step of filtering a material to be purified that contains an organic solvent using a filter to obtain the chemical solution.

[15] The method for producing a drug solution described in

[14] , wherein the filtration process is a multi-stage filtration process in which the material to be purified is passed through two or more types of filters that differ in at least one aspect selected from the group consisting of filter material, pore size, and pore structure.

[16] A method for producing a drug solution described in

[14] or

[15] , wherein when one filter is used, the filter has a pore diameter of 5 nm or less, and when two or more filters are used, the filter having the smallest pore diameter among the filters has a pore diameter of 5 nm or less. Effect of the Invention

[0008] According to the present invention, it is possible to provide a chemical solution that has excellent defect suppression performance even when applied to a resist process using EUV exposure. Also, the present invention can provide a method for producing the chemical solution. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram showing a typical example of a purification apparatus capable of carrying out a multistage filtration process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below. The following description of the components may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. In the present invention, "ppm" stands for "parts-per-million (10 -6 ) and "ppb" stands for "parts-per-billion (10 -9 )" and "ppt" stands for "parts-per-trillion (10 -12 )" and "ppq" is "parts-per-quadrillion(10 -15 )". In addition, in the description of groups (atomic groups) in the present invention, descriptions that do not indicate whether they are substituted or unsubstituted include those that have no substituents as well as those that have a substituent, within the scope of the present invention. For example, the term "hydrocarbon group" includes not only hydrocarbon groups that have no substituents (unsubstituted hydrocarbon groups), but also hydrocarbon groups that have a substituent (substituted hydrocarbon groups). This also applies to each compound. In the present invention, "radiation" refers to, for example, far ultraviolet light, extreme ultraviolet light (EUV), X-rays, electron beams, etc. In the present invention, light refers to actinic light rays or radiation. Unless otherwise specified, "exposure" in the present invention includes not only exposure to far ultraviolet light, X-rays, EUV, etc., but also drawing with particle beams such as electron beams or ion beams.

[0011] [Chemical solution] The chemical solution according to the embodiment of the present invention (hereinafter also referred to as "the chemical solution") contains an organic solvent and metal-containing particles containing metal atoms, and the number of metal nanoparticles having a particle diameter of 0.5 to 17 nm contained in the chemical solution is 1.0 × 10 1 ~1.0×10 9 pieces / cm 3 It is a medicinal liquid. Although the mechanism by which the present drug solution solves the above problems is not entirely clear, the present inventors speculate on the mechanism as follows: Note that the following mechanism is merely speculation, and even if the effect of the present invention is obtained through a different mechanism, it is still within the scope of the present invention.

[0012] This drug solution contains metal nanoparticles with a particle size of 0.5 to 17 nm, and the number of particles contained in the drug solution is 1.0 × 10 1 ~1.0×10 9 pieces / cm 3 One of the features of this system is that it is controlled to In processes in which EUV exposure is applied, there is a demand for narrowing of the resist pattern spacing, pattern width, and pattern pitch, which is the sum of a single pattern width and pattern spacing when these are periodically arranged, as well as the spacing, wiring width, and wiring pitch, which is the sum of a single wiring width and wiring spacing when these are periodically arranged, of the wiring to be manufactured. Specifically, the pattern width and / or pattern interval is often about 10 to 15 nm (in this case, the pattern pitch is often 20 to 30 nm). In such cases, the present inventors have found that it is necessary to control finer particles in units of their numbers, which has not been a major problem in conventional processes.

[0013] Among the above particles, metal-containing particles with a particle size of less than 0.5 nm tend to agglomerate more easily and often form coarse particles as a result. Therefore, they are often removed during the process (for example, by being washed away), and it is assumed that they do not have a significant impact on the defect suppression performance of the chemical solution. On the other hand, among the above particles, metal-containing particles with a particle diameter of more than 17 nm are sufficiently large compared to the desired resist pitch, and therefore, as mentioned above, are likely to be removed during the process, and it is presumed that their impact on the defect suppression performance of the chemical solution is not significant.

[0014] It is assumed that metal nanoparticles with a particle diameter of 0.5 to 17 nm tend to be more difficult to remove from the substrate. 1 pieces / cm 3 If the above conditions are met, the metal nanoparticles will be more likely to aggregate with each other and be more likely to be removed during the process, and as a result, it is presumed that the chemical solution will have excellent defect suppression performance. On the other hand, the number of metal nanoparticles per unit volume of the drug solution is 1.0 × 10 9 pieces / cm 3 It is presumed that if the metal nanoparticles themselves are prevented from causing defects when the thickness is below this range, the chemical solution has excellent defect suppression performance as a result. The content of metal nanoparticles in the chemical solution can be measured by the method described in the Examples, and the number of particles (number) of metal nanoparticles per unit volume of the chemical solution is rounded off to two significant digits.

[0015] [Organic Solvent] The chemical solution contains an organic solvent. The content of the organic solvent in the chemical solution is not particularly limited, but is generally preferably 98.0% by mass or more, more preferably 99.0% by mass or more, even more preferably 99.9% by mass or more, and particularly preferably 99.99% by mass or more, based on the total mass of the chemical solution. The upper limit is not particularly limited, but is often less than 100% by mass. The organic solvent may be used alone or in combination of two or more. When two or more organic solvents are used in combination, the total content is preferably within the above range.

[0016] In this specification, the organic solvent refers to a liquid organic compound contained in an amount exceeding 10,000 ppm by mass per component relative to the total mass of the chemical solution. In other words, in this specification, a liquid organic compound contained in an amount exceeding 10,000 ppm by mass relative to the total mass of the chemical solution corresponds to an organic solvent. In this specification, the term "liquid" means that the material is liquid at 25° C. and atmospheric pressure.

[0017] The type of the organic solvent is not particularly limited, and known organic solvents can be used. Examples of the organic solvent include alkylene glycol monoalkyl ether carboxylate, alkylene glycol monoalkyl ether, alkyl lactate, alkyl alkoxypropionate, cyclic lactone (preferably having 4 to 10 carbon atoms), monoketone compound which may have a ring (preferably having 4 to 10 carbon atoms), alkylene carbonate, alkyl alkoxyacetate, and alkyl pyruvate. In addition, as the organic solvent, for example, those described in JP-A-2016-057614, JP-A-2014-219664, JP-A-2016-138219, and JP-A-2015-135379 may be used.

[0018] As the organic solvent, at least one selected from the group consisting of propylene glycol monomethyl ether, propylene glycol monoethyl ether (PGME), propylene glycol monopropyl ether, propylene glycol monomethyl ether acetate (PGMEA), ethyl lactate (EL), methyl methoxypropionate, cyclopentanone, cyclohexanone (CHN), γ-butyrolactone, diisoamyl ether, butyl acetate (nBA), isoamyl acetate, isopropanol, 4-methyl-2-pentanol, dimethyl sulfoxide, n-methyl-2-pyrrolidone, diethylene glycol, ethylene glycol, dipropylene glycol, propylene glycol, ethylene carbonate, propylene carbonate (PC), sulfolane, cycloheptanone, 1-hexanol, decane, and 2-heptanone is preferred. Among them, CHN, PGMEA, PGME, nBA, PC, and mixtures thereof are preferred in that a chemical solution having a more excellent effect of the present invention can be obtained. The organic solvents may be used alone or in combination of two or more kinds. The type and content of the organic solvent in the chemical solution can be measured using a gas chromatograph mass spectrometer.

[0019] [Metal-containing particles] The chemical solution contains metal-containing particles that contain metal atoms. A preferred embodiment of the method for producing the present chemical solution will be described later, but in general, the present chemical solution can be produced by purifying a material to be purified that contains an organic solvent and impurities as described above. The metal-containing particles may be intentionally added in the production process of the chemical solution, may be originally contained in the material to be purified, or may be transferred (so-called contamination) from a chemical solution production device or the like during the production process of the chemical solution.

[0020] The metal atom is not particularly limited, and examples thereof include Fe atoms, Al atoms, Cr atoms, Ni atoms, Pb atoms, Zn atoms, and Ti atoms. In particular, when the content of metal-containing particles containing at least one selected from the group consisting of Fe atoms, Al atoms, Pb atoms, Zn atoms, and Ti atoms in the chemical solution is strictly controlled, better defect suppression performance is likely to be obtained, and when the content of metal-containing particles containing at least one selected from the group consisting of Pb atoms and Ti atoms in the chemical solution is strictly controlled, even better defect suppression performance is likely to be obtained. That is, the metal atom is preferably at least one selected from the group consisting of Fe atoms, Al atoms, Cr atoms, Ni atoms, Pb atoms, Zn atoms, Ti atoms, etc., more preferably at least one selected from the group consisting of Fe atoms, Al atoms, Pb atoms, Zn atoms, and Ti atoms, even more preferably at least one selected from the group consisting of Pb atoms and Ti atoms, and it is particularly preferable that the metal-containing particle contains both Pb atoms and Ti atoms. The metal-containing particles may contain one type of metal atom alone or two or more types of metal atoms in combination.

[0021] The particle diameter of the metal-containing particles is not particularly limited, but for example, in chemicals for manufacturing semiconductor devices, the content of particles having a particle diameter of about 0.1 to 100 nm in the chemicals is often subject to control. In particular, according to the study by the present inventors, it has been found that, in particular, in a chemical solution applied to a photoresist process for EUV exposure, by controlling the content of metal-containing particles (hereinafter also referred to as "metal nanoparticles") having a particle diameter of 0.5 to 17 nm in the chemical solution, a chemical solution having excellent defect suppression performance is easily obtained. As already explained, in a photoresist process for EUV exposure, fine resist intervals, resist widths, and resist pitches are often required. In such cases, it is required to control finer particles in units of their number, which was not much of a problem in conventional processes.

[0022] The particle size distribution based on the number of metal-containing particles is not particularly limited, but in order to obtain a chemical solution having a better effect of the present invention, it is preferable that the particle size distribution has a maximum value in at least one selected from the group consisting of a particle size range of less than 5 nm and a particle size range of more than 17 nm. In other words, it is preferable that the particle diameter does not have a maximum value in the range of 5 to 17 nm. By not having a maximum value in the range of 5 to 17 nm, the chemical solution has a better defect suppression performance, in particular, a better bridge defect suppression performance. Note that the bridge defect suppression performance means a defect evaluated by the method described in the examples. In order to obtain a liquid medicine having even better effects of the present invention, it is more preferable that the particle size distribution based on the number of particles has a maximum value in the particle size range of 0.5 nm or more and less than 5 nm. As a result, the liquid medicine has even better ability to suppress bridge defects.

[0023] <Metal nanoparticles> Metal nanoparticles refer to metal-containing particles with a particle diameter of 0.5 to 17 nm. The number of metal nanoparticles per unit volume of the solution is 1.0×10 1 ~1.0×10 9 pieces / cm 3 The drug solution has a more excellent effect of the present invention, and the number of particles contained is 1.0 × 10 2 pieces / cm 3 More than 1.0×10 is preferable. 3 pieces / cm 3 More preferably, 1.0×10 6 pieces / cm 3 Less than or equal to 1.0×10 is preferred. 5 pieces / cm 3 The following is more preferable: 1.x10 4 pieces / cm 3 The following is even more preferred: The number of metal nanoparticles per unit volume of the drug solution is 1.0×10 2 ~1.0×10 6 pieces / cm 3 In this case, the chemical solution has better defect suppression performance.

[0024] The metal atoms contained in the metal nanoparticles are not particularly limited, but are the same as the atoms already described as the metal atoms contained in the metal-containing particles. In particular, in terms of obtaining a drug solution having a more excellent effect of the present invention, the metal atoms are preferably at least one selected from the group consisting of Pb atoms and Ti atoms, and it is more preferable that the metal nanoparticles contain both Pb atoms and Ti atoms. In other words, the metal nanoparticles preferably contain at least one selected from the group consisting of metal nanoparticles containing Pb atoms (hereinafter also referred to as "Pb nanoparticles") and metal nanoparticles containing Ti atoms (hereinafter also referred to as "Ti nanoparticles"), and it is more preferable that the metal nanoparticles contain both Pb nanoparticles and Ti nanoparticles. The metal nanoparticles containing both Pb atoms and Ti atoms typically refer to a form in which the chemical solution contains both metal nanoparticles containing Pb atoms and metal nanoparticles containing Ti atoms.

[0025] The particle number ratio (Pb / Ti) of Pb nanoparticles and Ti nanoparticles contained in the chemical solution is not particularly limited, but is generally 1.0×10 -4 ~3.0 is preferred, 1.0×10 -3 ~2.0 is more preferable, and 1.0×10 -2 More preferably, Pb / Ti is 1.0×10 -3 When the viscosity is ≦2.0, the chemical solution has better effects of the present invention, in particular, better bridge defect suppression performance. The present inventors have found that Pb nanoparticles and Ti nanoparticles are likely to associate with each other, for example, when a chemical solution is applied to a wafer, and are likely to cause defects (particularly bridge defects) during development of a resist film. Pb / Ti is 1.0×10 -3 Surprisingly, when the ratio is 0.1 to 2.0, the occurrence of defects is more easily suppressed. In this specification, Pb / Ti, A / (B+C) described later, and U / V described later are calculated by rounding off the values ​​to two significant digits.

[0026] Metal nanoparticles may contain metal atoms, and there is no particular restriction on their form. Examples include a single metal atom, a compound containing a metal atom (hereinafter also referred to as a "metal compound"), and a composite of these. Metal nanoparticles may contain multiple metal atoms. When metal nanoparticles contain multiple metals, the metal atom with the highest content (atm%) among the multiple metals is the main component. Therefore, when Pb nanoparticles are mentioned, it means that when multiple metals are contained, Pb atoms are the main component among the multiple metals.

[0027] The composite is not particularly limited, but examples thereof include so-called core-shell type particles having a simple metal atom and a metal compound covering at least a part of the simple metal atom, solid solution particles containing a metal atom and other atoms, eutectic particles containing a metal atom and other atoms, aggregate particles of a simple metal atom and a metal compound, aggregate particles of different types of metal compounds, and metal compounds whose composition changes continuously or intermittently from the particle surface to the center.

[0028] The atoms other than the metal atom contained in the metal compound are not particularly limited, but examples thereof include carbon atoms, oxygen atoms, nitrogen atoms, hydrogen atoms, sulfur atoms, and phosphorus atoms, among which oxygen atoms are preferred. The form in which the metal compound contains an oxygen atom is not particularly limited, but an oxide of the metal atom is more preferred.

[0029] In terms of obtaining a chemical solution having a more excellent effect of the present invention, it is preferable that the metal nanoparticles are at least one type selected from the group consisting of particles consisting of simple metal atoms (particles A), particles consisting of oxides of metal atoms (particles B), and particles consisting of simple metal atoms and oxides of metal atoms (particles C). The relationship between the number of particles A, the number of particles B, and the number of particles C in the number of metal nanoparticles contained per unit volume of the chemical solution is not particularly limited. However, in order to obtain a chemical solution having a more excellent effect of the present invention, the ratio of the number of particles A to the total number of particles B and the number of particles C (hereinafter, also referred to as "A / (B+C)") is preferably 1.5 or less, more preferably less than 1.0, and more preferably 2.0×10 -1 Less than 1.0×10 is more preferable. -1 The following is particularly preferred: 1.0×10 -3 More than 1.0×10 is preferable. -2 The above is more preferable. When A / (B+C) is less than 1.0, the chemical solution has better bridge defect suppression performance, better pattern width uniformity performance, and better stain defect suppression performance. Also, A / (B+C) is 0.1 (1.0×10 -1 ) or less, the chemical solution has better residue defect suppression performance.

[0030] [Other ingredients] The chemical solution may contain other components in addition to those mentioned above, such as organic compounds other than organic solvents (particularly, organic compounds having a boiling point of 300° C. or higher), water, and resins.

[0031] <Organic compounds other than organic solvents> The chemical solution may contain an organic compound other than an organic solvent (hereinafter, also referred to as a "specific organic compound"). In this specification, a specific organic compound means an organic compound that is different from the organic solvent contained in the chemical solution and is contained in an amount of 10,000 ppm by mass or less with respect to the total mass of the chemical solution. In other words, in this specification, an organic compound that is contained in an amount of 10,000 ppm by mass or less with respect to the total mass of the chemical solution corresponds to a specific organic compound and does not correspond to an organic solvent. In addition, when multiple types of organic compounds are contained in a chemical solution and each organic compound is contained in an amount of 10,000 mass ppm or less as described above, each of the organic compounds corresponds to a specific organic compound.

[0032] The specific organic compound may be added to the chemical solution, or may be mixed unintentionally during the manufacturing process of the chemical solution. Examples of the case where the specific organic compound is mixed unintentionally during the manufacturing process of the chemical solution include the case where the specific organic compound is contained in a raw material (e.g., an organic solvent) used in the manufacturing of the chemical solution, and the case where the specific organic compound is mixed during the manufacturing process of the chemical solution (e.g., contamination), but are not limited to the above.

[0033] The content of the specific organic compound in the chemical solution can be measured using a gas chromatography mass spectrometry (GCMS).

[0034] The number of carbon atoms in the specific organic compound is not particularly limited, but in order for the chemical solution to have a better effect of the present invention, it is preferably 8 or more, and more preferably 12 or more. The upper limit of the number of carbon atoms is not particularly limited, but it is preferably 30 or less.

[0035] The specific organic compound may be, for example, a by-product generated in the synthesis of an organic solvent and / or an unreacted raw material (hereinafter, also referred to as "by-product, etc."). Examples of the by-products include compounds represented by the following formulas I to V.

[0036] [ka]

[0037] In formula I, R1 and R2 each independently represent an alkyl group or a cycloalkyl group, or are bonded together to form a ring.

[0038] The alkyl group or cycloalkyl group represented by R1 and R2 is preferably an alkyl group having 1 to 12 carbon atoms or a cycloalkyl group having 6 to 12 carbon atoms, and more preferably an alkyl group having 1 to 8 carbon atoms or a cycloalkyl group having 6 to 8 carbon atoms.

[0039] The ring formed by combining R1 and R2 with each other is a lactone ring, preferably a 4- to 9-membered lactone ring, more preferably a 4- to 6-membered lactone ring.

[0040] It is preferable that R1 and R2 satisfy the relationship such that the compound represented by formula I has 8 or more carbon atoms.

[0041] In formula II, R3 and R4 each independently represent a hydrogen atom, an alkyl group, an alkenyl group, a cycloalkyl group, or a cycloalkenyl group, or are bonded together to form a ring, provided that R3 and R4 are not both hydrogen atoms.

[0042] The alkyl group represented by R3 and R4 is, for example, preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 8 carbon atoms.

[0043] The alkenyl group represented by R3 and R4 is, for example, preferably an alkenyl group having 2 to 12 carbon atoms, and more preferably an alkenyl group having 2 to 8 carbon atoms.

[0044] The cycloalkyl group represented by R3 and R4 is preferably a cycloalkyl group having 6 to 12 carbon atoms, more preferably a cycloalkyl group having 6 to 8 carbon atoms.

[0045] The cycloalkenyl group represented by R3 and R4 is, for example, preferably a cycloalkenyl group having 3 to 12 carbon atoms, and more preferably a cycloalkenyl group having 6 to 8 carbon atoms.

[0046] The ring formed by R3 and R4 bonding to each other is a cyclic ketone structure, which may be a saturated cyclic ketone or an unsaturated cyclic ketone. This cyclic ketone is preferably a 6- to 10-membered ring, more preferably a 6- to 8-membered ring.

[0047] It is preferable that R3 and R4 satisfy the relationship such that the compound represented by formula II has 8 or more carbon atoms.

[0048] In formula III, R5 represents an alkyl group or a cycloalkyl group.

[0049] The alkyl group represented by R5 is preferably an alkyl group having 6 or more carbon atoms, more preferably an alkyl group having 6 to 12 carbon atoms, and further preferably an alkyl group having 6 to 10 carbon atoms. The alkyl group may have an ether bond in the chain, and may have a substituent such as a hydroxyl group.

[0050] The cycloalkyl group represented by R5 is preferably a cycloalkyl group having 6 or more carbon atoms, more preferably a cycloalkyl group having 6 to 12 carbon atoms, and even more preferably a cycloalkyl group having 6 to 10 carbon atoms.

[0051] In formula IV, R6 and R7 each independently represent an alkyl group or a cycloalkyl group, or are bonded together to form a ring.

[0052] The alkyl group represented by R6 and R7 is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 8 carbon atoms.

[0053] The cycloalkyl group represented by R6 and R7 is preferably a cycloalkyl group having 6 to 12 carbon atoms, more preferably a cycloalkyl group having 6 to 8 carbon atoms.

[0054] The ring formed by R6 and R7 bonding to each other is a cyclic ether structure. This cyclic ether structure is preferably a 4- to 8-membered ring, and more preferably a 5- to 7-membered ring.

[0055] It is preferable that R6 and R7 satisfy the relationship such that the compound represented by formula IV has 8 or more carbon atoms.

[0056] In formula V, R8 and R9 each independently represent an alkyl group or a cycloalkyl group, or are bonded to each other to form a ring, and L represents a single bond or an alkylene group.

[0057] The alkyl group represented by R8 and R9 is, for example, preferably an alkyl group having 6 to 12 carbon atoms, and more preferably an alkyl group having 6 to 10 carbon atoms.

[0058] The cycloalkyl group represented by R8 and R9 is preferably a cycloalkyl group having 6 to 12 carbon atoms, more preferably a cycloalkyl group having 6 to 10 carbon atoms.

[0059] The ring formed by R8 and R9 bonding to each other is a cyclic diketone structure. This cyclic diketone structure is preferably a 6- to 12-membered ring, and more preferably a 6- to 10-membered ring.

[0060] The alkylene group represented by L is, for example, preferably an alkylene group having 1 to 12 carbon atoms, and more preferably an alkylene group having 1 to 10 carbon atoms. Incidentally, R8, R9 and L satisfy the relationship such that the compound represented by formula V has 8 or more carbon atoms. Although not particularly limited, in the case where the organic solvent is an amide compound, an imide compound, or a sulfoxide compound, in one embodiment, an amide compound, an imide compound, or a sulfoxide compound having 6 or more carbon atoms can be mentioned. In addition, examples of the specific organic compound include the following compounds.

[0061] [ka]

[0062] [ka]

[0063] Further, examples of specific organic compounds include antioxidants such as dibutylhydroxytoluene (BHT), distearyl thiodipropionate (DSTP), 4,4'-butylidenebis-(6-t-butyl-3-methylphenol), 2,2'-methylenebis-(4-ethyl-6-t-butylphenol), and the antioxidants described in JP 2015-200775 A; unreacted raw materials; structural isomers and by-products generated during the production of organic solvents; leachates from components constituting organic solvent production equipment (for example, plasticizers leachate from rubber components such as O-rings); and the like.

[0064] In addition, specific organic compounds include dioctyl phthalate (DOP), bis(2-ethylhexyl) phthalate (DEHP), bis(2-propylheptyl) phthalate (DPHP), dibutyl phthalate (DBP), benzyl butyl phthalate (BBzP), diisodecyl phthalate (DIDP), diisooctyl phthalate (DIOP), diethyl phthalate (DEP), diisobutyl phthalate (DIBP), dihexyl phthalate, diisononyl phthalate (DINP), tris(2-ethylhexyl) trimellitate (TEHTM), tris(n-octyl- n-Decyl) (ATM), bis(2-ethylhexyl) adipate (DEHA), monomethyl adipate (MMAD), dioctyl adipate (DOA), dibutyl sebacate (DBS), dibutyl maleate (DBM), diisobutyl maleate (DIBM), azelaic acid esters, benzoic acid esters, terephthalates (e.g., dioctyl terephthalate (DEHT)), diisononyl 1,2-cyclohexanedicarboxylate (DINCH), epoxidized vegetable oils, sulfonamides (e.g., N-(2-hydroxypropyl)benzenesulfonamide (HP BSA), N-(n-butyl)benzenesulfonamide (BBSA-NBBS)), organic phosphate esters (e.g., tricresyl phosphate (TCP), tributyl phosphate (TBP)), acetylated monoglycerides, triethyl citrate (TEC), acetyl triethyl citrate (ATEC), tributyl citrate (TBC), acetyl tributyl citrate (ATBC), trioctyl citrate (TOC), acetyl trioctyl citrate (ATOC), trihexyl citrate (THC), acetyl trihexyl citrate (ATHC), epoxidized soybean oil, ethylene propylene rubber, polybutene, addition polymers of 5-ethylidene-2-norbornene, and polymeric plasticizers exemplified below are also included. These specific organic compounds are presumed to be mixed into the product or chemical solution from filters, piping, tanks, O-rings, containers, etc. that come into contact with the product or chemical solution during the refining process. In particular, compounds other than alkyl olefins are associated with the occurrence of bridge defects.

[0065] [ka]

[0066] (Organic compounds with a boiling point of 300°C or higher) The chemical solution may contain, among the specific organic compounds, an organic compound with a boiling point of 300°C or higher (a high boiling point organic compound). When the chemical solution contains an organic compound with a boiling point of 300°C or higher, the boiling point is high and it is difficult to volatilize during the photolithography process. Therefore, in order to obtain a chemical solution with excellent defect suppression performance, it is necessary to strictly control the content and the form of existence of the high boiling point organic compound in the chemical solution. Examples of such high boiling point organic compounds that have been confirmed include dioctyl phthalate (boiling point 385°C), diisononyl phthalate (boiling point 403°C), dioctyl adipate (boiling point 335°C), dibutyl phthalate (boiling point 340°C), and ethylene propylene rubber (boiling point 300 to 450°C).

[0067] The present inventors have found that when a high-boiling organic compound is contained in a chemical solution, it can take various forms. Examples of the form in which the high-boiling organic compound exists in the chemical solution include particles in which particles made of metal atoms or metal compounds and particles of a high-boiling organic compound are aggregated; particles made of metal atoms or metal compounds and particles of a high-boiling organic compound arranged so as to cover at least a part of the particles; particles formed by coordinate bonds between metal atoms and a high-boiling organic compound; and the like.

[0068] Among these, metal nanoparticles (particles U) containing an organic compound (preferably a high-boiling organic compound) are cited as a form that has a large effect on the defect suppression performance of the chemical solution. The present inventors have found that by controlling the number of particles U contained per unit volume of the chemical solution, the defect suppression performance of the chemical solution is dramatically improved. Although the reason for this is not entirely clear, the particles U tend to have a relatively small surface free energy compared to metal nanoparticles (particles V) that do not contain an organic compound (preferably, a high-boiling organic compound). Such particles U are less likely to remain on a substrate treated with a chemical solution, and even if they remain, they are more likely to be removed when they come into contact with the chemical solution again. For example, when a chemical solution is used as a developer and a rinse solution, the particles U are less likely to remain on the substrate during development, and are more likely to be removed by rinsing, etc. That is, as a result, both the organic compound (preferably, a high-boiling organic compound) and the particles containing metal atoms are more likely to be removed. Furthermore, since resist films are generally water-repellent, it is assumed that particles U, which have a lower surface energy, are less likely to remain on the substrate.

[0069] The ratio of the number of particles U contained in a unit volume of the liquid to the number of particles V contained in the unit volume of the liquid is preferably 10 (1.0×10) or more, since a liquid having a more excellent effect of the present invention can be obtained. 1 ) or more is preferable, and 1.0×10 2 Preferably, it is 50 or less, more preferably 35 or less, and particularly preferably 25 or less.

[0070] <Water> The chemical solution may contain water. The water is not particularly limited, and for example, distilled water, ion-exchanged water, pure water, etc. can be used. Water is not included in the organic impurities. Water may be added to the chemical solution, or may be mixed unintentionally into the chemical solution during the manufacturing process of the chemical solution. Examples of cases where water is mixed unintentionally during the manufacturing process of the chemical solution include, but are not limited to, cases where water is contained in a raw material (e.g., an organic solvent) used in the manufacturing of the chemical solution, and cases where water is mixed during the manufacturing process of the chemical solution (e.g., contamination).

[0071] The water content in the liquid chemical is not particularly limited, but is generally preferably 0.05 to 2.0% by mass based on the total mass of the liquid chemical. The water content in the liquid chemical means the water content measured using an apparatus that uses the Karl Fischer water content measurement method as the measurement principle.

[0072] <Resin> The chemical solution may further contain a resin. The resin is preferably a resin P having a group that decomposes under the action of an acid to generate a polar group. The resin is more preferably a resin having a repeating unit represented by formula (AI) described later, which is a resin whose solubility in a developer mainly composed of an organic solvent decreases under the action of an acid. The resin having a repeating unit represented by formula (AI) described later has a group that decomposes under the action of an acid to generate an alkali-soluble group (hereinafter, also referred to as an "acid-decomposable group"). The polar group may be an alkali-soluble group, such as a carboxy group, a fluorinated alcohol group (preferably a hexafluoroisopropanol group), a phenolic hydroxyl group, or a sulfo group.

[0073] In the acid-decomposable group, the polar group is protected by a group that is detached by an acid (acid-detachable group). Examples of the acid-detachable group include -C(R 36 )(R 37 )(R 38 ), -C(R 36 )(R 37 )(OR 39 ), and -C(R 01 )(R 02 )(OR 39 ) etc.

[0074] In the formula, R 36 ~R 39 R each independently represents an alkyl group, a cycloalkyl group, an aryl group, an aralkyl group, or an alkenyl group. 36 and R 37 may be bonded to each other to form a ring.

[0075] R 01 and R 02each independently represents a hydrogen atom, an alkyl group, a cycloalkyl group, an aryl group, an aralkyl group, or an alkenyl group.

[0076] The resin P, the solubility of which in a developer mainly composed of an organic solvent decreases due to the action of an acid, will be described in detail below.

[0077] (Formula (AI): Repeating unit having an acid-decomposable group) Resin P preferably contains a repeating unit represented by formula (AI).

[0078] [ka]

[0079] In formula (AI), Xa1 represents a hydrogen atom or an alkyl group which may have a substituent. T represents a single bond or a divalent linking group. Ra1 to Ra3 each independently represent an alkyl group (straight-chain or branched-chain) or a cycloalkyl group (monocyclic or polycyclic). Two of Ra1 to Ra3 may be bonded to form a cycloalkyl group (monocyclic or polycyclic).

[0080] Examples of the alkyl group represented by Xa1 which may have a substituent include a methyl group and -CH2-R 11 Examples of the group represented by R 11 represents a halogen atom (such as a fluorine atom), a hydroxyl group, or a monovalent organic group. Xa1 is preferably a hydrogen atom, a methyl group, a trifluoromethyl group or a hydroxymethyl group.

[0081] Examples of the divalent linking group for T include an alkylene group, a -COO-Rt- group, and a -O-Rt- group, in which Rt represents an alkylene group or a cycloalkylene group. T is preferably a single bond or a -COO-Rt- group. Rt is preferably an alkylene group having 1 to 5 carbon atoms, more preferably a -CH2- group, a -(CH2)2- group, or a -(CH2)3- group.

[0082] The alkyl groups Ra1 to Ra3 are preferably those having 1 to 4 carbon atoms.

[0083] The cycloalkyl group of Ra1 to Ra3 is preferably a monocyclic cycloalkyl group such as a cyclopentyl group or a cyclohexyl group, or a polycyclic cycloalkyl group such as a norbornyl group, a tetracyclodecanyl group, a tetracyclododecanyl group, or an adamantyl group. The cycloalkyl group formed by combining two of Ra1 to Ra3 is preferably a monocyclic cycloalkyl group such as a cyclopentyl group or a cyclohexyl group, or a polycyclic cycloalkyl group such as a norbornyl group, a tetracyclodecanyl group, a tetracyclododecanyl group, an adamantyl group, etc. A monocyclic cycloalkyl group having 5 to 6 carbon atoms is more preferable.

[0084] The cycloalkyl group formed by combining two of Ra1 to Ra3 may have, for example, one of the methylene groups constituting the ring replaced with a heteroatom such as an oxygen atom, or a group having a heteroatom such as a carbonyl group.

[0085] In the repeating unit represented by formula (AI), for example, Ra1 is a methyl group or an ethyl group, and Ra2 and Ra3 are bonded to form the above-mentioned cycloalkyl group.

[0086] Each of the above groups may have a substituent. Examples of the substituent include an alkyl group (having 1 to 4 carbon atoms), a halogen atom, a hydroxyl group, an alkoxy group (having 1 to 4 carbon atoms), a carboxy group, and an alkoxycarbonyl group (having 2 to 6 carbon atoms), and the like, preferably having 8 or less carbon atoms.

[0087] The content of the repeating unit represented by formula (AI) is preferably from 20 to 90 mol %, more preferably from 25 to 85 mol %, and even more preferably from 30 to 80 mol %, based on all repeating units in the resin P.

[0088] (Repeating unit having a lactone structure) In addition, the resin P preferably contains a repeating unit Q having a lactone structure.

[0089] The repeating unit Q having a lactone structure preferably has a lactone structure in the side chain, and is more preferably a repeating unit derived from a (meth)acrylic acid derivative monomer. The repeating unit Q having a lactone structure may be used alone or in combination of two or more kinds, but it is preferable to use one kind alone. The content of the repeating unit Q having a lactone structure is preferably from 3 to 80 mol %, more preferably from 3 to 60 mol %, based on all repeating units in the resin P.

[0090] The lactone structure is preferably a 5- to 7-membered lactone structure, and more preferably a structure in which another ring structure is condensed with the 5- to 7-membered lactone structure to form a bicyclo structure or a spiro structure. The lactone structure preferably has a repeating unit having a lactone structure represented by any one of the following formulae (LC1-1) to (LC1-17). The lactone structure is preferably a lactone structure represented by formula (LC1-1), formula (LC1-4), formula (LC1-5), or formula (LC1-8), and more preferably a lactone structure represented by formula (LC1-4).

[0091] [ka]

[0092] The lactone structure portion may have a substituent (Rb2). Preferred examples of the substituent (Rb2) include an alkyl group having 1 to 8 carbon atoms, a cycloalkyl group having 4 to 7 carbon atoms, an alkoxy group having 1 to 8 carbon atoms, an alkoxycarbonyl group having 2 to 8 carbon atoms, a carboxy group, a halogen atom, a hydroxyl group, a cyano group, and an acid-decomposable group. n2 represents an integer of 0 to 4. When n2 is 2 or more, the multiple substituents (Rb2) may be the same or different, and the multiple substituents (Rb2) may be bonded to each other to form a ring.

[0093] (Repeating unit having a phenolic hydroxyl group) Furthermore, the resin P may contain a repeating unit having a phenolic hydroxyl group. An example of the repeating unit having a phenolic hydroxyl group is a repeating unit represented by the following general formula (I).

[0094] [ka]

[0095] During the ceremony, R 41 , R 42 and R 43 each independently represents a hydrogen atom, an alkyl group, a halogen atom, a cyano group, or an alkoxycarbonyl group. 42 may be bonded to Ar4 to form a ring, in which case R 42 represents a single bond or an alkylene group.

[0096] X4 is a single bond, -COO-, or -CONR 64 - represents R 64 represents a hydrogen atom or an alkyl group. L4 represents a single bond or an alkylene group. Ar4 represents an (n+1)-valent aromatic ring group; R 42 When it bonds with the ring, it represents an (n+2)-valent aromatic ring group. n represents an integer of 1 to 5.

[0097] R in general formula (I) 41 , R 42 and R 43 The alkyl group may have a substituent, and is preferably an alkyl group having 20 or less carbon atoms, such as a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a hexyl group, a 2-ethylhexyl group, an octyl group, or a dodecyl group, more preferably an alkyl group having 8 or less carbon atoms, and even more preferably an alkyl group having 3 or less carbon atoms.

[0098] R in general formula (I) 41 , R 42 and R 43 The cycloalkyl group may be a monocyclic or polycyclic cycloalkyl group, and is preferably a monocyclic cycloalkyl group having 3 to 8 carbon atoms, such as a cyclopropyl group, a cyclopentyl group, or a cyclohexyl group, which may have a substituent.

[0099] R in general formula (I) 41 , R 42 and R 43 Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom, with a fluorine atom being preferred.

[0100] R in general formula (I) 41 , R 42 and R 43 The alkyl group contained in the alkoxycarbonyl group of R 41 , R 42 and R 43 The same alkyl groups as those in the above are preferred.

[0101] Examples of the substituent in each of the above groups include an alkyl group, a cycloalkyl group, an aryl group, an amino group, an amido group, a ureido group, a urethane group, a hydroxy group, a carboxy group, a halogen atom, an alkoxy group, a thioether group, an acyl group, an acyloxy group, an alkoxycarbonyl group, a cyano group, and a nitro group, and the number of carbon atoms of the substituent is preferably 8 or less.

[0102] Ar4 represents an aromatic ring group having a valence of (n+1). When n is 1, the divalent aromatic ring group may have a substituent, and examples thereof include arylene groups having 6 to 18 carbon atoms, such as a phenylene group, a tolylene group, a naphthylene group, and an anthracenylene group, and aromatic ring groups containing a heterocycle, such as thiophene, furan, pyrrole, benzothiophene, benzofuran, benzopyrrole, triazine, imidazole, benzimidazole, triazole, thiadiazole, and thiazole.

[0103] Specific examples of the (n+1)-valent aromatic ring group when n is an integer of 2 or more include groups obtained by removing any (n-1) hydrogen atoms from the above-mentioned specific examples of the divalent aromatic ring group. The (n+1)-valent aromatic ring group may further have a substituent.

[0104] Examples of the substituent that the above-mentioned alkyl group, cycloalkyl group, alkoxycarbonyl group, alkylene group, and (n+1)-valent aromatic ring group may have include R 41 , R 42 and R 43 alkoxy groups such as a methoxy group, an ethoxy group, a hydroxyethoxy group, a propoxy group, a hydroxypropoxy group, and a butoxy group; and aryl groups such as a phenyl group.

[0105] -CONR represented by X4 64 -(R 64 represents a hydrogen atom or an alkyl group. 64 Examples of the alkyl group include alkyl groups having 20 or less carbon atoms, such as a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a hexyl group, a 2-ethylhexyl group, an octyl group, and a dodecyl group, which may have a substituent, and an alkyl group having 8 or less carbon atoms is more preferable.

[0106] X4 is preferably a single bond, -COO- or -CONH-, more preferably a single bond or -COO-.

[0107] The alkylene group in L4 is preferably an alkylene group having 1 to 8 carbon atoms, such as a methylene group, an ethylene group, a propylene group, a butylene group, a hexylene group, or an octylene group, which may have a substituent.

[0108] Ar4 is preferably an aromatic ring group having 6 to 18 carbon atoms which may have a substituent, and more preferably a benzene ring group, a naphthalene ring group or a biphenylene ring group.

[0109] The repeating unit represented by formula (I) preferably has a hydroxystyrene structure, that is, Ar4 is preferably a benzene ring group.

[0110] The content of the repeating unit having a phenolic hydroxyl group relative to all repeating units in the resin P is preferably from 0 to 50 mol %, more preferably from 0 to 45 mol %, and even more preferably from 0 to 40 mol %.

[0111] (Repeating unit containing an organic group having a polar group) Resin P may further contain a repeating unit containing an organic group having a polar group, in particular a repeating unit having an alicyclic hydrocarbon structure substituted with a polar group, which improves the substrate adhesion and developer affinity. The alicyclic hydrocarbon structure substituted with a polar group is preferably an adamantyl group, a diamantyl group, or a norbornane group, and the polar group is preferably a hydroxyl group or a cyano group.

[0112] When the resin P contains a repeating unit containing an organic group having a polar group, the content thereof is preferably 1 to 50 mol %, more preferably 1 to 30 mol %, still more preferably 5 to 25 mol %, and particularly preferably 5 to 20 mol %, based on the total repeating units in the resin P.

[0113] (Repeating unit represented by formula (VI)) Resin P may contain a repeating unit represented by the following general formula (VI).

[0114] [ka]

[0115] In general formula (VI), R 61 , R 62 and R 63 each independently represents a hydrogen atom, an alkyl group, a cycloalkyl group, a halogen atom, a cyano group, or an alkoxycarbonyl group. 62 may be bonded to Ar6 to form a ring, in which case R 62 represents a single bond or an alkylene group. X6 is a single bond, -COO-, or -CONR 64 - stands for R 64 represents a hydrogen atom or an alkyl group. L6 represents a single bond or an alkylene group. Ar6 represents an (n+1)-valent aromatic ring group; R 62 When it bonds with the ring, it represents an (n+2)-valent aromatic ring group. When n is 2 or more, each Y2 independently represents a hydrogen atom or a group which is eliminated by the action of an acid, provided that at least one Y2 represents a group which is eliminated by the action of an acid. n represents an integer of 1 to 4.

[0116] As the group Y2 which is eliminated by the action of an acid, a structure represented by the following general formula (VI-A) is preferable.

[0117] [ka]

[0118] L1 and L2 each independently represent a hydrogen atom, an alkyl group, a cycloalkyl group, an aryl group, or a group formed by combining an alkylene group with an aryl group. M represents a single bond or a divalent linking group. Q represents an alkyl group, a cycloalkyl group which may contain a heteroatom, an aryl group which may contain a heteroatom, an amino group, an ammonium group, a mercapto group, a cyano group, or an aldehyde group. At least two of Q, M and L1 may be bonded to form a ring (preferably a 5- or 6-membered ring).

[0119] The repeating unit represented by the above general formula (VI) is preferably a repeating unit represented by the following general formula (3).

[0120] [ka]

[0121] In general formula (3), Ar3 represents an aromatic ring group. R3 represents a hydrogen atom, an alkyl group, a cycloalkyl group, an aryl group, an aralkyl group, an alkoxy group, an acyl group, or a heterocyclic group. M3 represents a single bond or a divalent linking group. Q3 represents an alkyl group, a cycloalkyl group, an aryl group or a heterocyclic group. At least two of Q3, M3 and R3 may be combined to form a ring.

[0122] The aromatic ring group represented by Ar3 is the same as Ar6 in the above general formula (VI) when n is 1, and is preferably a phenylene group or a naphthylene group, more preferably a phenylene group.

[0123] (Repeating unit having silicon atom in the side chain) The resin P may further contain a repeating unit having a silicon atom in the side chain. Examples of the repeating unit having a silicon atom in the side chain include a (meth)acrylate repeating unit having a silicon atom and a vinyl repeating unit having a silicon atom. The repeating unit having a silicon atom in the side chain is typically a repeating unit having a group having a silicon atom in the side chain, and examples of the group having a silicon atom include a trimethylsilyl group, a triethylsilyl group, a triphenylsilyl group, a tricyclohexylsilyl group, a tristrimethylsiloxysilyl group, a tristrimethylsilylsilyl group, a methylbistrimethylsilylsilyl group, a methylbistrimethylsiloxysilyl group, a dimethyltrimethylsilylsilyl group, a dimethyltrimethylsiloxysilyl group, and the following cyclic or linear polysiloxanes, or cage, ladder, or random silsesquioxane structures. In the formula, R and R 1 each independently represents a monovalent substituent. * represents a bond.

[0124] [ka]

[0125] Preferred examples of the repeating unit having the above group include a repeating unit derived from an acrylate compound or methacrylate compound having the above group, or a repeating unit derived from a compound having the above group and a vinyl group.

[0126] When the resin P has the repeating unit having a silicon atom in the side chain, the content thereof is preferably 1 to 30 mol %, more preferably 5 to 25 mol %, and even more preferably 5 to 20 mol %, based on all repeating units in the resin P.

[0127] The weight average molecular weight of the resin P, as calculated as a polystyrene equivalent by GPC (gel permeation chromatography), is preferably 1,000 to 200,000, more preferably 3,000 to 20,000, and even more preferably 5,000 to 15,000. By setting the weight average molecular weight to 1,000 to 200,000, deterioration of heat resistance and dry etching resistance can be prevented, and deterioration of developability and deterioration of film formability due to an increase in viscosity can be prevented.

[0128] The dispersity (molecular weight distribution) is usually 1 to 5, preferably 1 to 3, more preferably 1.2 to 3.0, and even more preferably 1.2 to 2.0.

[0129] In the chemical solution, the content of the resin P is preferably 50 to 99.9 mass % of the total solid content, and more preferably 60 to 99.0 mass %. In the chemical solution, the resin P may be used alone or in combination with a plurality of resins.

[0130] Other components contained in the chemical solution (e.g., acid generator, basic compound, quencher, hydrophobic resin, surfactant, solvent, etc.) may be any known components. Examples of other components include those contained in actinic ray-sensitive or radiation-sensitive resin compositions described in JP2013-195844A, JP2016-057645A, JP2015-207006A, WO2014 / 148241A, JP2016-188385A, and JP2017-219818A.

[0131] [Use of chemicals] The chemical solutions according to the above embodiments are preferably used in the manufacture of semiconductor devices, and more preferably used to form fine patterns with a node of 10 nm or less (for example, a process including pattern formation using EUV). The chemical liquid according to the above embodiment is further preferably used as a chemical liquid (pre-wet liquid, developer, rinse liquid, resist liquid solvent, stripper liquid, etc.) used in a resist process in which the pattern width and / or pattern spacing is 17 nm or less (preferably 15 nm or less, more preferably 12 nm or less) and / or the resulting wiring width and / or wiring spacing is 17 nm or less, in other words, for manufacturing a semiconductor device manufactured using a resist film in which the pattern width and / or pattern spacing is 17 nm or less.

[0132] Specifically, in the manufacturing process of semiconductor devices including a lithography process, an etching process, an ion implantation process, a stripping process, etc., it is used to treat organic matter after the completion of each process or before moving to the next process, and specifically, it is suitably used as a pre-wet liquid, a developer, a rinse liquid, a stripping liquid, etc. For example, it can also be used to rinse the edge line of a semiconductor substrate before and after resist coating. The chemical liquid can also be used as a diluting liquid for the resin contained in the resist liquid, or as a solvent contained in the resist liquid. The chemical liquid may also be diluted with other organic solvents and / or water.

[0133] Furthermore, the above-mentioned chemical solution can be used for purposes other than the manufacture of semiconductor devices, and can also be used as a developer for polyimide, resist for sensors, resist for lenses, etc., and as a rinse solution, etc. The chemical liquid can also be used as a solvent for medical or cleaning purposes, and is particularly suitable for cleaning containers, pipes, and substrates (e.g., wafers, glass, etc.).

[0134] In particular, this chemical solution exerts superior effects when applied to a pre-wet solution, developer, and rinse solution in pattern formation using EUV (extreme ultraviolet) rays.

[0135] [Method of manufacturing chemicals] The method for producing the above-mentioned chemical solution is not particularly limited, and any known production method can be used. Among them, the method for producing the chemical solution preferably includes a filtration step of filtering the product to be purified containing an organic solvent using a filter to obtain the chemical solution, in order to obtain a chemical solution having a more excellent effect of the present invention.

[0136] The material to be purified used in the filtration process is procured by purchase or the like, and obtained by reacting raw materials. As the material to be purified, it is preferable to use the metal-containing particles and / or the material with a small content of impurities as described above. Examples of commercially available products of such materials to be purified include those called "high purity grade products."

[0137] The method of reacting raw materials to obtain a product to be purified (typically a product to be purified containing an organic solvent) is not particularly limited, and any known method can be used. For example, there is a method of reacting one or more raw materials in the presence of a catalyst to obtain an organic solvent. More specifically, for example, there is a method of reacting acetic acid with n-butanol in the presence of sulfuric acid to obtain butyl acetate; a method of reacting ethylene, oxygen, and water in the presence of Al(C2H5)3 to obtain 1-hexanol; a method of reacting cis-4-methyl-2-pentene in the presence of Ipc2BH (Diisopinocampheylborane) to obtain 4-methyl-2-pentanol; a method of reacting propylene oxide, methanol, and acetic acid in the presence of sulfuric acid to obtain PGMEA (propylene glycol 1-monomethyl ether 2-acetate); a method of reacting acetone and hydrogen in the presence of copper oxide-zinc oxide-aluminum oxide to obtain IPA (isopropyl alcohol); and a method of reacting lactic acid and ethanol to obtain ethyl lactate.

[0138] <Filtration process> The method for producing a chemical solution according to an embodiment of the present invention includes a filtering step of filtering the material to be purified using a filter to obtain a chemical solution. The method for filtering the material to be purified using a filter is not particularly limited, but it is preferable to pass the material to be purified (liquid) through a filter unit having a housing and a cartridge filter housed in the housing with or without pressure.

[0139] Filter pore size The pore size of the filter is not particularly limited, and a filter having a pore size that is usually used for filtering a product to be purified can be used. In particular, the pore size of the filter is preferably 200 nm or less, more preferably 20 nm or less, even more preferably 10 nm or less, particularly preferably 5 nm or less, and most preferably 3 nm or less, in that the number of particles having a particle size of 0.5 to 17 nm contained in the drug solution can be easily controlled within a desired range. The lower limit is not particularly limited, but generally, 1 nm or more is preferable from the viewpoint of productivity. In this specification, the pore size and pore size distribution of the filter refer to the pore size and pore size distribution determined by the bubble point of isopropanol (IPA) or HFE-7200 ("Novec 7200", manufactured by 3M, hydrofluoroether, C4F9OC2H5).

[0140] It is preferable that the pore size of the filter is 5.0 nm or less, since it is easier to control the number of particles having a diameter of 0.5 to 17 nm contained in the drug solution. Hereinafter, a filter having a pore size of 5 nm or less is also referred to as a "micropore filter". The micropore filter may be used alone or in combination with a filter having a different pore size. In particular, it is preferable to use the micropore filter in combination with a filter having a larger pore size from the viewpoint of superior productivity. In this case, clogging of the micropore filter can be prevented by passing the product to be purified that has been previously filtered through a filter having a larger pore size through the micropore filter. That is, when one filter is used, the pore size of the filter is preferably 5.0 nm or less, and when two or more filters are used, the pore size of the filter having the smallest pore size is preferably 5.0 nm or less.

[0141] The form of using two or more filters with different pore sizes in sequence is not particularly limited, but includes a method of arranging the filter units described above in sequence along the pipeline through which the purified product is transported. In this case, if the flow rate per unit time of the purified product is to be constant throughout the entire pipeline, a filter unit with a smaller pore size may be subjected to a larger pressure than a filter unit with a larger pore size. In this case, it is preferable to arrange a pressure regulating valve and a damper between the filter units to make the pressure applied to the filter unit with a smaller pore size constant, or to arrange filter units containing the same filter in parallel along the pipeline to increase the filtration area. In this way, the number of particles of 0.5 to 17 nm contained in the drug solution can be more stably controlled.

[0142] Filter material The material of the filter is not particularly limited, and any known filter material can be used. Specifically, in the case of a resin, polyamides such as 6-nylon and 6,6-nylon; polyolefins such as polyethylene and polypropylene; polystyrene; polyimide; polyamideimide; poly(meth)acrylate; polytetrafluoroethylene, perfluoroalkoxyalkane, perfluoroethylenepropene copolymer, ethylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer, polychlorotrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, and polyvinyl fluoride; polyvinyl alcohol; polyester; cellulose; cellulose acetate, and the like can be mentioned. Among them, at least one selected from the group consisting of nylon (especially 6,6-nylon is preferable), polyolefins (especially polyethylene is preferable), poly(meth)acrylate, and polyfluorocarbons (especially polytetrafluoroethylene (PTFE) and perfluoroalkoxyalkane (PFA) are preferable) is preferable, because they have better solvent resistance and the resulting chemical solution has better defect suppression performance. These polymers may be used alone or in combination of two or more. In addition to resin, materials such as diatomaceous earth and glass may also be used.

[0143] The filter may be surface-treated. The method of surface treatment is not particularly limited, and any known method can be used. Examples of the surface treatment method include chemical modification, plasma treatment, hydrophobic treatment, coating, gas treatment, and sintering.

[0144] The plasma treatment is preferred because it makes the filter surface hydrophilic. The water contact angle on the filter surface that has been hydrophilized by the plasma treatment is not particularly limited, but the static contact angle at 25°C measured with a contact angle meter is preferably 60° or less, more preferably 50° or less, and even more preferably 30° or less.

[0145] As the chemical modification treatment, a method of introducing an ion exchange group into the base material is preferable. That is, the filter is preferably one in which the above-mentioned materials are used as a substrate and an ion exchange group is introduced into the substrate. Typically, a filter including a substrate having an ion exchange group on the surface is preferred. The surface-modified substrate is not particularly limited, and the above-mentioned polymer is preferably one in which an ion exchange group is introduced, in terms of easier production.

[0146] Examples of the ion exchange group include a sulfonic acid group, a carboxyl group, and a phosphoric acid group as a cation exchange group, and a quaternary ammonium group as an anion exchange group. The method for introducing the ion exchange group into the polymer is not particularly limited, but includes a method in which a compound having an ion exchange group and a polymerizable group is reacted with the polymer to typically perform grafting.

[0147] The method for introducing ion exchange groups is not particularly limited, but may be to irradiate fibers of the above resin with ionizing radiation (alpha rays, beta rays, gamma rays, X-rays, electron beams, etc.) to generate active moieties (radicals) in the resin. The irradiated resin is immersed in a monomer-containing solution to graft polymerize the monomer onto the substrate. As a result, the monomer is bonded to the polyolefin fiber as a graft-polymerized side chain. The resin having the generated polymer as a side chain is contacted and reacted with a compound having an anion exchange group or a cation exchange group, whereby the ion exchange group is introduced into the graft-polymerized side chain polymer to obtain the final product.

[0148] The filter may also be constructed by combining a woven or nonwoven fabric on which ion exchange groups are formed by radiation-induced graft polymerization with a conventional filtering material such as glass wool, woven or nonwoven fabric.

[0149] By using a filter having an ion exchange group, the content of particles containing metal atoms in the chemical solution can be easily controlled to a desired range. The material of the filter having an ion exchange group is not particularly limited, but examples thereof include polyfluorocarbon and polyolefin having an ion exchange group introduced therein, and polyfluorocarbon having an ion exchange group introduced therein is more preferable. The pore size of the filter having an ion exchange group is not particularly limited, but is preferably 1 to 30 nm, more preferably 5 to 20 nm. The filter having an ion exchange group may also serve as the filter having the smallest pore size described above, or may be used separately from the filter having the smallest pore size. In particular, in order to obtain a chemical solution having a more excellent effect of the present invention, the filtration step is preferably performed using a filter having an ion exchange group and a filter having a smallest pore size without an ion exchange group. The material of the filter having the minimum pore size already described is not particularly limited, but from the viewpoint of solvent resistance and the like, generally, at least one selected from the group consisting of polyfluorocarbons and polyolefins is preferred, and polyolefins are more preferred.

[0150] Furthermore, when the filter material is polyamide (particularly nylon), the content of the high boiling point organic compound and the particles U in the chemical solution can be more easily controlled, and in particular, the content of the particles U in the chemical solution can be even more easily controlled. Therefore, it is preferable to use two or more filters made of different materials as the filters used in the filtration process, and it is more preferable to use two or more filters selected from the group consisting of polyolefins, polyfluorocarbons, polyamides, and these filters into which ion exchange groups have been introduced.

[0151] -Porous structure of the filter The pore structure of the filter is not particularly limited and may be appropriately selected depending on the components in the product to be purified. In this specification, the pore structure of the filter means the pore size distribution, the positional distribution of the pores in the filter, the shape of the pores, etc., and can typically be controlled by the manufacturing method of the filter. For example, porous membranes can be obtained by sintering powders of resins or the like, and fibrous membranes can be obtained by electrospinning, electroblowing, meltblowing, and other methods, each of which has a different pore structure.

[0152] By "porous membrane" is meant a membrane that retains components of a product, such as gels, particles, colloids, cells, and poly-oligomers, but allows components substantially smaller than the pores to pass through the pores. Retention of components of a product by a porous membrane can depend on operating conditions, such as face velocity, use of surfactants, pH, and combinations thereof, and can depend on the pore size, structure, and size and structure of the particles to be removed (such as hard particles or gels).

[0153] When the product to be purified contains particles U (which may be in the form of a gel) as impurities, particles containing high boiling point organic compounds are often negatively charged, and a polyamide filter serves as a non-sieving membrane to remove such particles. Typical non-sieving membranes include nylon membranes such as nylon-6 membrane and nylon-6,6 membrane, but are not limited to these. It is noted that, as used herein, "non-sieving" retention mechanisms refer to retention that occurs due to mechanisms such as obstruction, diffusion and adsorption that are not related to the pressure drop or pore size of the filter.

[0154] Non-sieving retention includes retention mechanisms such as obstruction, diffusion and adsorption that remove target particles in the product regardless of the pressure drop of the filter or the pore size of the filter. Particle adsorption to the filter surface can be mediated, for example, by intermolecular van der Waals and electrostatic forces. Obstruction effects occur when particles moving through a non-sieving membrane layer with a tortuous path cannot change direction quickly enough to avoid contact with the non-sieving membrane. Particle transport by diffusion results primarily from the random or Brownian motion of small particles, which creates a certain probability of the particles colliding with the filter media. Non-sieving retention mechanisms can be active when there is no repulsive force between the particles and the filter.

[0155] UPE (ultra-high molecular weight polyethylene) filters are typically sieving membranes, meaning membranes that capture particles primarily through a sieving retention mechanism or that are optimized for capturing particles through a sieving retention mechanism. Typical examples of sieving membranes include, but are not limited to, polytetrafluoroethylene (PTFE) membranes and UPE membranes. The "sieve retention mechanism" refers to the retention of particles that are larger than the pore size of the porous membrane. Sieve retention can be improved by forming a filter cake (an agglomeration of particles to be removed on the membrane surface). The filter cake effectively performs the function of a secondary filter.

[0156] The material of the fiber layer is not particularly limited as long as it is a polymer capable of forming a fiber layer. Examples of the polymer include polyamides. Examples of the polyamide include nylon 6 and nylon 6,6. The polymer forming the fiber membrane may be poly(ethersulfone). When the fiber membrane is on the primary side of the porous membrane, it is preferable that the surface energy of the fiber membrane is higher than that of the polymer that is the material of the porous membrane on the secondary side. An example of such a combination is when the material of the fiber membrane is nylon and the porous membrane is polyethylene (UPE).

[0157] The method for producing the fiber membrane is not particularly limited, and any known method can be used, including, for example, electrospinning, electroblowing, and meltblowing.

[0158] The pore structure of the porous membrane (e.g., porous membranes containing UPE, PTFE, etc.) is not particularly limited, but examples of the pore shape include lace-like, string-like, and node-like. The distribution of pore sizes in the porous membrane and the distribution of their positions in the membrane are not particularly limited. The size distribution may be smaller and the distribution positions in the membrane may be symmetric. The size distribution may be larger and the distribution positions in the membrane may be asymmetric (the above membrane is also called "asymmetric porous membrane"). In an asymmetric porous membrane, the size of the pores changes in the membrane, and typically the pore size increases from one surface of the membrane to the other surface of the membrane. In this case, the surface on the side where there are more pores with large pore sizes is called the "open side", and the surface on the side where there are more pores with small pore sizes is also called the "tight side". Asymmetric porous membranes include, for example, those in which the pore size is smallest at a position within the thickness of the membrane (also called "hourglass shaped").

[0159] With an asymmetric porous membrane, the primary side has larger pore size, in other words the primary side is the open side, which can create a pre-filtration effect.

[0160] The porous membrane may include a thermoplastic polymer such as PESU (polyethersulfone), PFA (perfluoroalkoxyalkane, a copolymer of tetrafluoroethylene and perfluoroalkoxyalkane), polyamide, and polyolefin, or may include polytetrafluoroethylene, etc. Among them, ultra-high molecular weight polyethylene is preferable as a material for the porous membrane. Ultra-high molecular weight polyethylene means a thermoplastic polyethylene having an extremely long chain, and preferably has a molecular weight of at least one million, typically 2 to 6 million.

[0161] The filter used in the filtration step is preferably two or more types of filters with different pore structures, more preferably a filter made of a porous membrane and a filter made of a fiber membrane. Specifically, it is preferable to use a filter made of a nylon fiber membrane and a filter made of a UPE porous membrane in combination.

[0162] As described above, the filtration process according to the embodiment of the present invention is preferably a multistage filtration process in which the material to be purified is passed through two or more types of filters that differ in at least one aspect selected from the group consisting of filter material, pore size, and pore structure.

[0163] (Multi-stage filtration process) The multistage filtration process can be carried out using a known purification device. Fig. 1 is a schematic diagram showing a typical example of a purification device capable of carrying out the multistage filtration process. The purification device 10 has a production tank 11, a filtration device 16, and a filling device 13, and each of the above units is connected by a pipeline 14. Filtration device 16 has filter units 12(a) and 12(b) connected by a pipeline 14. A regulating valve 15(a) is disposed in the pipeline between filter units 12(a) and 12(b). Although FIG. 1 illustrates a case where the number of filter units is two, three or more filter units may be used.

[0164] In Fig. 1, the product to be purified is stored in a production tank 11. Next, a pump (not shown) arranged in a pipeline 14 is operated, and the product to be purified is sent from the production tank 11 through the pipeline 14 to a filtration device 16. The transport direction of the product to be purified in the purification device 10 is indicated by F1 in Fig. 1.

[0165] Filtration device 16 is composed of filter units 12(a) and 12(b) connected by a pipeline 14, and each of the two filter units contains a cartridge filter having filters that differ in at least one type selected from the group consisting of pore size, material, and pore structure. Filtration device 16 has a function of filtering the product to be purified that is supplied through the pipeline. Although there are no particular limitations on the filters housed in each filter unit, it is preferable that the filter having the smallest pore size is housed in filter unit 12(b).

[0166] As the pump operates, the product is supplied to filter unit 12(a) and filtered. The product filtered by filter unit 12(a) is depressurized by regulating valve 15(a) as necessary, and is supplied to filter unit 12(b) and filtered.

[0167] The refining device does not necessarily have to have regulating valve 15(a). Even if it has regulating valve 15(a), its position does not have to be on the upstream side of filter unit 12(b) and may be on the upstream side of filter unit 12(a). Moreover, a device capable of adjusting the supply pressure of the product to be purified may be used other than a regulating valve. Examples of such a device include a damper.

[0168] In addition, in the filtration device 16, each filter forms a cartridge filter, but the filter that can be used in the purification method according to the present embodiment is not limited to the above-mentioned form. For example, the filter may be a form in which the product to be purified is passed through a filter formed in a flat plate shape.

[0169] In addition, in the above-mentioned purification device 10, the purified product after filtering through the filter unit 12(b) is transferred to the filling device 13 and stored in a container, but the filtration device for carrying out the above-mentioned purification method is not limited to the above, and may be configured to return the purified product filtered through the filter unit 12(b) to the production tank 11 and pass it through the filter unit 12(a) and the filter unit 12(b) again. The above-mentioned filtration method is called circulating filtration. In the purification of the purified product by circulating filtration, at least one of two or more types of filters is used two or more times. In this specification, the operation of returning the filtered purified product filtered by each filter unit to the production tank is counted as one circulation. The number of circulation times may be appropriately selected depending on the components in the product to be purified.

[0170] The material of the liquid-contacting part of the above-mentioned purification device (meaning the inner wall surface with which the product to be purified and the chemical liquid may come into contact, etc.) is not particularly limited, but is preferably made of at least one selected from the group consisting of non-metallic materials and electrolytically polished metallic materials (hereinafter, these are also collectively referred to as "corrosion-resistant material"). For example, when the liquid-contacting part of a production tank is made of a corrosion-resistant material, it can be meant that the production tank itself is made of a corrosion-resistant material, or the inner wall surface of the production tank is coated with a corrosion-resistant material.

[0171] The non-metallic material is not particularly limited, and any known material can be used. Examples of non-metallic materials include, but are not limited to, at least one selected from the group consisting of polyethylene resin, polypropylene resin, polyethylene-polypropylene resin, tetrafluoroethylene resin, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer resin, tetrafluoroethylene-ethylene copolymer resin, trifluorochloroethylene-ethylene copolymer resin, vinylidene fluoride resin, trifluorochloroethylene copolymer resin, and vinyl fluoride resin.

[0172] The metal material is not particularly limited, and any known material can be used. The metal material may be, for example, a metal material in which the total content of chromium and nickel is more than 25 mass% based on the total mass of the metal material, and more preferably 30 mass% or more. The upper limit of the total content of chromium and nickel in the metal material is not particularly limited, but is preferably 90 mass% or less. Examples of metal materials include stainless steel and nickel-chromium alloys.

[0173] The stainless steel is not particularly limited, and known stainless steels can be used. Among them, an alloy containing 8% or more by mass of nickel is preferable, and an austenitic stainless steel containing 8% or more by mass of nickel is more preferable. Examples of austenitic stainless steel include SUS (Steel Use Stainless) 304 (Ni content 8% by mass, Cr content 18% by mass), SUS304L (Ni content 9% by mass, Cr content 18% by mass), SUS316 (Ni content 10% by mass, Cr content 16% by mass), and SUS316L (Ni content 12% by mass, Cr content 16% by mass).

[0174] The nickel-chromium alloy is not particularly limited, and any known nickel-chromium alloy can be used. Among them, a nickel-chromium alloy having a nickel content of 40 to 75 mass % and a chromium content of 1 to 30 mass % is preferable. Examples of nickel-chromium alloys include Hastelloy (trade name, the same applies below), Monel (trade name, the same applies below), and Inconel (trade name, the same applies below), etc. More specifically, examples include Hastelloy C-276 (Ni content 63 mass%, Cr content 16 mass%), Hastelloy-C (Ni content 60 mass%, Cr content 17 mass%), and Hastelloy C-22 (Ni content 61 mass%, Cr content 22 mass%), etc. Furthermore, the nickel-chromium alloy may further contain boron, silicon, tungsten, molybdenum, copper, cobalt, and the like, in addition to the above-mentioned alloy, as required.

[0175] The method for electrolytically polishing the metal material is not particularly limited, and any known method can be used, such as those described in paragraphs 0011 to 0014 of JP 2015-227501 A and paragraphs 0036 to 0042 of JP 2008-264929 A.

[0176] It is presumed that the chromium content in the surface passive layer of the metal material becomes higher than the chromium content in the parent phase by electrolytic polishing, and therefore, it is presumed that the use of a refining device in which the liquid-contacting parts are formed from an electrolytically polished metal material makes it difficult for metal-containing particles to flow out into the product to be refined. The metal material may be buffed. The method of buffing is not particularly limited, and known methods can be used. The size of the polishing grains used for finishing the buffing is not particularly limited, but #400 or less is preferable because it tends to reduce the unevenness of the surface of the metal material. The buffing is preferably performed before the electrolytic polishing.

[0177] <Other processes> The method for producing a chemical solution according to the embodiment of the present invention is not particularly limited as long as it includes a filtration step, and may further include steps other than the filtration step. Examples of the steps other than the filtration step include a distillation step, a reaction step, and a static electricity removal step.

[0178] (Distillation process) The distillation step is a step of distilling a purification target material containing an organic solvent to obtain a distilled purification target material. The method of distilling the purification target material is not particularly limited, and a known method can be used. A typical example is a method in which a distillation column is disposed on the primary side of the purification apparatus already described, and the distilled purification target material is introduced into a production tank. In this case, the liquid-contacting parts of the distillation column are not particularly limited, but are preferably made of the corrosion-resistant materials already described.

[0179] (Reaction process) The reaction process is a process in which the raw material is reacted to produce a product to be purified that contains an organic solvent as a reactant. The method for producing the product to be purified is not particularly limited, and a known method can be used. A typical example is a method in which a reaction tank is disposed on the primary side of the production tank (or distillation column) of the purification apparatus already described, and the reactant is introduced into the production tank (or distillation column). In this case, the liquid-contacting parts of the reaction vessel are not particularly limited, but are preferably made of the corrosion-resistant materials already described.

[0180] (static elimination process) The charge removal step is a step of removing static electricity from the material to be purified, thereby reducing the charged potential of the material to be purified. The method for removing static electricity is not particularly limited, and any known method for removing static electricity can be used. For example, the method for removing static electricity includes contacting the product to be purified with a conductive material. The contact time of the material to be purified with the conductive material is preferably 0.001 to 60 seconds, more preferably 0.001 to 1 second, and even more preferably 0.01 to 0.1 seconds. Examples of the conductive material include stainless steel, gold, platinum, diamond, and glassy carbon. As a method for contacting the material to be purified with a conductive material, for example, a grounded mesh made of a conductive material is placed inside the pipeline and the material to be purified is passed through the mesh.

[0181] It is preferable that the purification of the target substance, the opening of the container, the cleaning of the container and the device, the storage of the solution, and the analysis, which are associated with the purification, are all performed in a clean room. The clean room is preferably a clean room with a cleanliness of class 4 or higher as defined by the international standard ISO14644-1:2015 established by the International Organization for Standardization. Specifically, it is preferable that the clean room satisfies any one of ISO class 1, ISO class 2, ISO class 3, and ISO class 4, more preferably ISO class 1 or ISO class 2, and even more preferably ISO class 1.

[0182] The storage temperature of the drug solution is not particularly limited, but a storage temperature of 4°C or higher is preferable because impurities contained in trace amounts in the drug solution are less likely to be eluted, resulting in a more excellent effect of the present invention.

[0183] [Drug solution container] The drug solution produced by the above purification method may be stored in a container until it is used. Such a container and the chemical solution (or resist composition) contained therein are collectively referred to as a chemical solution container. The chemical solution is taken out of the stored chemical solution container and used.

[0184] The container for storing the above-mentioned chemical solution is preferably one that is highly clean inside and has little elution of impurities for use in semiconductor device manufacturing. Specific examples of containers that can be used include the "Clean Bottle" series manufactured by Aicello Chemical Co., Ltd. and the "Pure Bottle" manufactured by Kodama Resin Industry Co., Ltd., but are not limited to these.

[0185] As the container, it is also preferable to use a multi-layer bottle whose inner wall has a six-layer structure made of six types of resin, or a multi-layer bottle whose inner wall has a seven-layer structure made of six types of resin, in order to prevent impurities from being mixed in (contaminated) with the drug solution. Examples of such containers include the containers described in JP 2015-123351 A.

[0186] The liquid-contacting portion of the container is preferably made of the corrosion-resistant material or glass described above. In order to obtain a better effect of the present invention, it is preferable that 90% or more of the area of ​​the liquid-contacting portion is made of the above material, and it is more preferable that the entire liquid-contacting portion is made of the above material. EXAMPLES

[0187] The present invention will be described in more detail below based on examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.

[0188] In addition, in preparing the chemical solutions in the Examples and Comparative Examples, the handling of containers, preparation, filling, storage, and analysis of the chemical solutions were all performed in clean rooms that met ISO class 2 or 1. In order to improve measurement accuracy, when measuring the content of organic impurities and the content of metal atoms that are below the detection limit in normal measurements, the chemical solutions were concentrated to 1 / 100th of their volume and the content was calculated by converting it into the concentration of the solution before concentration. Note that the surfaces of the equipment used for purification, as well as tools such as filters and containers, that came into contact with the chemical solutions were thoroughly washed with chemical solutions that had been purified in the same manner before use.

[0189] [Purification of drug solution 1] A product to be purified (commercially available product) containing cyclohexanone (CHN) as an organic solvent was prepared, and filtered using a purification device similar to that shown in FIG. 1, except that the device had four filter units arranged in series along a pipeline, had a filtration device without an adjustment valve, and had a pipeline that could return the filtered product to the production tank after filtering in the most downstream filter unit, to produce a chemical solution. The following filters were arranged in each filter unit from the primary side. (In Table 1, they are listed as the first to fourth filters, respectively.) Polypropylene filter (pore size: 200 nm, porous membrane, indicated as "PP" in the table) -Polyfluorocarbon filter with ion exchange groups (pore size: 20 nm, fiber membrane made of polymers of PTFE and PES (polyethylene sulfonic acid), indicated as "IEX" in the table) Nylon filter (pore size: 10 nm, fiber membrane, listed as "Nylon" in the table) -UPE filter (pore size: 3 nm, porous membrane, indicated as "UPE" in the table) The purified product that had passed through the four filter units was returned to the production tank, and this process was repeated eight times to obtain a drug solution.

[0190] [Purification of chemical solutions 2 to 30] Chemical solutions 2 to 30 were obtained by purifying the material to be purified containing the organic solvents listed in Table 1 under the conditions listed in Table 1. Each chemical solution was obtained by passing the material to be purified through each filter listed in Table 1 in order from the first filter to the fourth filter (a chemical solution with a blank filter column indicates that the filter was not used. For example, chemical solution 2 was passed through the first filter to the fourth filter), and repeating this process the number of times listed in the "circulation count." The materials to be purified listed in Table 1 were procured from different lots, and therefore the components other than the organic solvents initially contained in each material may differ.

[0191] The abbreviations in Table 1 represent the following: PGMEA / PGME (7:3): A 7:3 (v / v) mixture of PGMEA and PGME nBA: n-Butyl acetate ·iAA: Isoamyl acetate ·MIBC: Methyl isobutyl carbinol IPA: Isopropanol PC / PGMEA (1:9): A 1:9 (v / v) mixture of PC and PGMEA EL: Ethyl lactate IEX / 10nm: IEX filter with pore size of 10nm PTFE: Polytetrafluoroethylene filter (porous membrane) UPE: Ultra-high molecular weight polyethylene filter (porous membrane) Nylon: Nylon filter (fiber membrane)

[0192] [Table 1]

[0193] [Evaluation of the number of particles with diameters of 0.5 to 17 nm contained in a drug solution] The content (number of particles contained) of particles having a particle diameter of 0.5 to 17 nm in the drug solution was measured by the following method. First, a certain amount of chemical solution was applied onto a silicon substrate to form a substrate with a chemical solution layer, and the surface of the substrate with the chemical solution layer was scanned with a laser beam to detect scattered light. This allowed the positions and particle sizes of defects present on the surface of the substrate with the chemical solution layer to be identified. Next, elemental analysis was performed using EDX (energy dispersive X-ray) analysis based on the positions of the defects to investigate the composition of the defects. This method was used to determine the number of particles of metal nanoparticles, Pb nanoparticles, and Ti nanoparticles on the substrate, and this was calculated as the number of particles contained per unit volume of the chemical solution (particles / cm). 3 The particle size distribution of the metal nanoparticles was also determined by the above method. Similarly, the composition of the metal nanoparticles (metal element and metal atom oxide) and the association state with high-boiling organic compounds were also identified. For the analysis, a combination of KLA-Tencor's wafer inspection tool "SP-5" and Applied Materials' fully automated defect review and classification tool "SEMVision G6" was used. In addition, the presence or absence of high boiling point organic compounds was measured using gas chromatography mass spectrometry.

[0194] For samples in which particles of the desired particle size could not be detected due to the resolution of the measuring device, etc., the method described in paragraphs 0015 to 0067 of JP 2009-188333 A was used to detect the particles. X A layer was formed, and then a chemical solution layer was formed so as to cover the layer. X The method used was to dry etch a composite layer having a layer and a chemical solution layer applied thereon, irradiate the resulting protrusions with light, detect scattered light, calculate the volume of the protrusions from the scattered light, and calculate the particle diameter from the volume of the protrusions. The measurement results for each chemical solution and the particle number ratio calculated based on the measurement results are shown in Table 2.

[0195] In Table 2, the abbreviations in the particle size distribution represent particles having particle sizes in the following ranges. "Less than 0.5": Metal-containing particles with a particle size of less than 0.5 nm "0.5-3": Metal nanoparticles with a particle size of 0.5 nm or more and less than 3 nm "3-5": Metal nanoparticles with a particle size of 3 nm or more and less than 5 nm "5-17": Metal nanoparticles with a particle size of 5 nm or more and 17 nm or less

[0196] [Table 2]

[0197] [Table 3]

[0198] Table 2 is divided into Table 2 (part 1) and Table 2 (part 2). The measurement results of each chemical solution are listed in the corresponding rows of the two tables. For example, Chemical Solution 1 uses cyclohexanone as the organic solvent, and contains 1.0×10 metal nanoparticles. 4 pieces / cm 3 The particle size distribution (number %) of the metal-containing particles is as follows: 20% of the metal-containing particles have a particle size of less than 0.5 nm, 50% of the metal nanoparticles have a particle size of 0.5 nm or more and less than 3 nm, 20% of the metal nanoparticles have a particle size of 3 nm or more and less than 5 nm, and 10% of the metal nanoparticles have a particle size of 5 nm or more and 17 nm or less. Particle A accounts for 2% of the total metal nanoparticles by number, and the total of particles B and C accounts for 98%, so that A / (B+C) is 2.0×10 -2 The metal nanoparticles contain high-boiling organic compounds, and the particle U accounts for 94% of the total number of metal nanoparticles, and the particle V accounts for 6% of the total number of metal nanoparticles, with a U / V ratio of 1.6×10 1 Among the metal nanoparticles, Pb nanoparticles are 1.3 × 10 2 pieces / cm 3 and Ti nanoparticles are 5.4 × 10 2 pieces / cm 3 and Pb / Ti is 2.4×10 -1 The other chemical solutions are listed in the table in the same manner as Chemical Solution 1.

[0199] [Example 1] The above-prepared chemical solution 1 was used as a pre-wetting solution to evaluate defect suppression performance. The resist compositions used were as follows:

[0200] [Resist Composition 1] Resist composition 1 was obtained by mixing the components in the following ratio. ·Resin (A-1): 0.77g Acid generator (B-1): 0.03g Basic compound (E-3): 0.03g PGMEA: 67.5g EL: 75g

[0201] <Resin (A) etc.> (Synthesis Example 1) Synthesis of Resin (A-1) 600 g of cyclohexanone was placed in a 2L flask and substituted with nitrogen at a flow rate of 100 mL / min for one hour. Then, 4.60 g (0.02 mol) of polymerization initiator V-601 (manufactured by Wako Pure Chemical Industries, Ltd.) was added, and the temperature was raised to 80°C. Next, the following monomers and 4.60 g (0.02 mol) of polymerization initiator V-601 (manufactured by Wako Pure Chemical Industries, Ltd.) were dissolved in 200 g of cyclohexanone to prepare a monomer solution. The monomer solution was added dropwise to the flask heated to 80°C over 6 hours. After the dropwise addition, the reaction was continued at 80°C for another 2 hours. 4-Acetoxystyrene 48.66g (0.3mol) 1-Ethylcyclopentyl methacrylate 109.4g (0.6mol) Monomer 1 22.2g (0.1mol)

[0202] [ka]

[0203] The reaction solution was cooled to room temperature and dropped into 3 L of hexane to precipitate the polymer. The filtered solid was dissolved in 500 mL of acetone and dropped again into 3 L of hexane. The filtered solid was dried under reduced pressure to obtain 160 g of 4-acetoxystyrene / 1-ethylcyclopentyl methacrylate / monomer 1 copolymer (A-1).

[0204] In a reaction vessel, 10 g of the polymer obtained above, 40 mL of methanol, 200 mL of 1-methoxy-2-propanol, and 1.5 mL of concentrated hydrochloric acid were added, heated to 80° C., and stirred for 5 hours. The reaction solution was allowed to cool to room temperature and dropped into 3 L of distilled water. The filtered solid was dissolved in 200 mL of acetone, dropped again into 3 L of distilled water, and the filtered solid was dried under reduced pressure to obtain resin (A-1) (8.5 g). The weight average molecular weight (Mw) in terms of standard polystyrene measured by gel permeation chromatography (GPC) (solvent: THF (tetrahydrofuran)) was 11200, and the molecular weight dispersity (Mw / Mn) was 1.45. The composition and other information are shown in Table 3 below.

[0205] [Table 4]

[0206] <Photoacid generator (B)> The photoacid generator used was as follows:

[0207] [ka]

[0208] <Basic Compound (E)> The following basic compounds were used:

[0209] [ka]

[0210] (Residue defect suppression performance, bridge defect suppression performance, and stain defect suppression performance) The chemicals were evaluated for their ability to suppress residue defects, bridge defects, and stain defects by the following methods. 3S " was used. First, AL412 (manufactured by Brewer Science) was applied onto a silicon wafer and baked at 200°C for 60 seconds to form a resist underlayer film with a thickness of 20 nm. A pre-wet liquid (chemical solution 1) was applied thereon, and resist composition 1 was applied thereon, followed by baking at 100°C for 60 seconds (PB: Prebake) to form a resist film with a thickness of 30 nm.

[0211] This resist film was exposed to light through a reflective mask with a pitch of 20 nm and a pattern width of 15 nm using an EUV exposure machine (manufactured by ASML; NXE3350, NA 0.33, Dipole 90°, outer sigma 0.87, inner sigma 0.35). It was then baked at 85° C. for 60 seconds (PEB: Post Exposure Bake). It was then developed with an organic solvent-based developer for 30 seconds and rinsed for 20 seconds. The wafer was then rotated at 2000 rpm for 40 seconds to form a line-and-space pattern with a pitch of 20 nm and a pattern line width of 15 nm.

[0212] An image of the above pattern was obtained, and the obtained image was analyzed using the above analytical device to measure the number of residues in the unexposed area per unit area (referred to as "residue defect suppression performance" in Table 4), and the number of bridge-like defects between patterns (number of bridge defects, referred to as "bridge defect suppression performance" in Table 4). In addition, defects in which no metal atoms were detected as a result of EDX (energy dispersive X-ray analysis) at the coordinates where defects were detected were defined as stain-like defects and were counted (referred to as "stain-like defect suppression performance" in Table 4). The results were evaluated according to the following criteria and shown in Table 4. In the following evaluation criteria, "number of defects" refers to the number of residue defects, the number of bridge defects, and the number of stain-like defects, respectively.

[0213] AA: Fewer than 30 defects. A: The number of defects was more than 30 but less than 60. B: The number of defects was 60 or more but less than 90. C: The number of defects was 90 or more and less than 120. D: The number of defects was 120 or more but less than 150. E: The number of defects was 150 or more but less than 180. F: The number of defects was 180 or more.

[0214] (Uniformity of pattern width) The image of the above pattern was acquired, and the obtained image was analyzed using the above analysis device to obtain LWR (Line Width Roughness). That is, when observing from above the pattern, the distance from the center of the pattern to the edge was observed at an arbitrary point, and the measurement variation was evaluated at 3σ. The results were evaluated according to the following criteria, and were used to evaluate the uniformity of the pattern width. The results are shown in Table 4.

[0215] AA:3σ was less than 1.5 nm. A: 3σ was greater than 1.5 nm and less than 1.8 nm. B: 3σ was greater than or equal to 1.8 nm and less than 2.2 nm. C: 3σ was greater than or equal to 2.2 nm and less than 2.5 nm. D: 3σ was greater than 2.5 nm and less than 2.8 nm. E:3σ was greater than or equal to 2.8 nm and less than 3.1 nm. F:3σ was greater than 3.1 nm.

[0216] [Examples 2 to 21 and Examples 23 to 28] The performance of suppressing residue defects, the performance of suppressing bridge defects, the performance of suppressing stain defects, and the performance of uniformity of pattern width of each chemical liquid were evaluated in the same manner as above, except that chemical liquids 2 to 21 and chemical liquids 23 to 28 were used instead of chemical liquid 1. The results are shown in Table 4.

[0217] [Comparative Examples 1 and 2] The performance in suppressing residue defects, the performance in suppressing bridge defects, the performance in suppressing stain defects, and the uniformity of pattern width were evaluated in the same manner as above, except that chemical solutions 29 and 30 were used instead of chemical solution 1. The results are shown in Table 4.

[0218] [Example 22] Except for not using a pre-wet liquid and using the chemical solution 22 as the developer, the chemical solution 22 was evaluated in terms of the residue defect suppression performance, bridge defect suppression performance, stain defect suppression performance, and pattern width uniformity performance in the same manner as above. The results are shown in Table 4.

[0219] [Table 5]

[0220] [Example 29] Resist composition 2, which is a chemical solution, was obtained using the same method and components as those for resist composition 1, except that 67.5 g of PGMEA and 75 g of EL in resist composition 1 were replaced with 67.5 g of PGMEA and 75 g of EL purified by the purification method for chemical solution 1 described in Example 1.

[0221] Next, for resist composition 2, the number of particles with diameters of 0.5 to 17 nm contained in the chemical solution was evaluated using the same method as above, and it was found to be approximately the same as in Example 1. In addition, a pattern was formed in the same manner as in Example 1, except that resist composition 2 was used and no pre-wet liquid was used. The residue defect suppression performance, bridge defect suppression performance, pattern width uniformity performance, and stain defect suppression performance were investigated, and the results were similar to those of Example 1.

[0222] From the results in Table 4, it can be seen that the chemical solutions described in Examples 1 to 21 and Examples 23 to 28, when used as pre-wetting solutions, had excellent residue defect suppression performance, excellent bridge defect suppression performance, excellent pattern width uniformity performance, and excellent stain defect suppression performance. Furthermore, from the results of Table 4, when the chemical solution described in Example 22 was used as a developer, it was found that it had excellent residue defect suppression performance, excellent bridge defect suppression performance, excellent pattern width uniformity performance, and excellent stain defect suppression performance.

[0223] Furthermore, the chemical solution of Example 29, as a resist solution, had excellent performance in suppressing residue defects, excellent performance in suppressing bridge defects, excellent performance in uniformity of pattern width, and excellent performance in suppressing stain defects.

[0224] Chemical solution 1, which had a maximum value in the particle diameter range of 0.5 nm or more and less than 5 nm, had better residue defect suppression performance, better bridge defect suppression performance, better pattern width uniformity performance, and better stain defect suppression performance than chemical solution 8. Also, chemical solution 1 had even better bridge defect suppression performance than chemical solution 9.

[0225] Compared with chemical solution 10, in which A / (B+C) is less than 1.0, chemical solution 1 had better residue defect suppression performance, better bridge defect suppression performance, better pattern width uniformity performance, and better stain defect suppression performance.

[0226] A / (B+C) is 1.0×10 -1 Compared to chemical solution 12, chemical solution 1 shown below had better residue defect suppression performance, better bridge defect suppression performance, better pattern width uniformity performance, and better stain defect suppression performance.

[0227] U / V is 1.0×10 1 Compared with chemical solution 16, chemical solution 1 as described above had better residue defect suppression performance, better bridge defect suppression performance, better pattern width uniformity performance, and better stain defect suppression performance.

[0228] Pb / Ti is 1.0×10 -3Chemical solution 1, which has a refractive index of 1.0 or less or 2.0 or less, had better residue defect suppression performance, better bridge defect suppression performance, better pattern width uniformity performance, and better stain defect suppression performance than chemical solution 17 and chemical solution 20. [Explanation of symbols]

[0229] 10 Purification equipment 11 Production Tank 12(a), 12(b) Filter unit 13 Filling equipment 14 Conduit 15(a) Regulating valves 16 Filtration equipment

Claims

1. An organic solvent; Metal-containing particles containing metal atoms; A drug solution containing Among the metal-containing particles, the number of metal nanoparticles having a particle diameter of 0.5 to 17 nm contained per unit volume of the drug solution is 1.0 × 10 1 ~1.0 x 10 9 pieces / cm 3 That is, liquid medicine.

2. 2. The chemical solution according to claim 1, wherein a particle size distribution based on the number of the metal-containing particles has a maximum value in at least one range selected from the group consisting of a particle size range of less than 5 nm and a particle size range of more than 17 nm.

3. The drug solution according to claim 2 , wherein the particle size distribution has a maximum value in a particle size range of 0.5 nm or more and less than 5 nm.

4. The chemical solution according to any one of claims 1 to 3, which is used in the manufacture of a semiconductor device.

5. The chemical solution according to any one of claims 1 to 4, wherein the metal nanoparticles are at least one type selected from the group consisting of particles A consisting of a simple substance of the metal atom, particles B consisting of an oxide of the metal atom, and particles C consisting of a simple substance of the metal atom and an oxide of the metal atom.

6. The chemical solution according to claim 5, wherein a ratio of the number of particles A contained per unit volume of the chemical solution to the sum of the number of particles B contained and the number of particles C contained per unit volume of the chemical solution is less than 1.

0.

7. The particle number ratio is 1.0×10 -1 The drug solution according to claim 5 or 6, wherein:

8. The chemical solution according to any one of claims 1 to 7, further comprising an organic compound having a boiling point of 300°C or higher.

9. The chemical solution according to claim 8 , wherein at least a portion of the metal nanoparticles are particles U containing the organic compound.

10. At least a portion of the metal nanoparticles are Particles U containing the organic compound, and The particle V does not contain an organic compound, The ratio of the number of particles U contained in the chemical solution to the number of particles V contained in the chemical solution per unit volume is 1.0 × 10 1 The drug solution according to claim 8 or 9.

11. The chemical solution according to any one of claims 1 to 10, wherein the metal nanoparticles contain at least one selected from the group consisting of metal nanoparticles containing Pb atoms and metal nanoparticles containing Ti atoms.

12. The chemical solution according to any one of claims 1 to 11, wherein the metal nanoparticles contain the metal nanoparticles containing the Pb atoms and the metal nanoparticles containing the Ti atoms.

13. The ratio of the number of metal nanoparticles containing Pb atoms to the number of metal nanoparticles containing Ti atoms per unit volume of the chemical solution is 1.0 × 10 -3 The drug solution according to any one of claims 1 to 12, wherein the viscosity is 2.0 or less.

14. A method for producing the chemical solution according to any one of claims 1 to 13, comprising a filtration step of filtering a material to be purified that contains an organic solvent using a filter to obtain the chemical solution.

15. 15. The method for producing a chemical solution according to claim 14, wherein the filtration step is a multistage filtration step in which the product to be purified is passed through two or more types of filters that differ in at least one property selected from the group consisting of filter material, pore size, and pore structure.

16. 16. The method for producing a drug solution according to claim 14 or 15, wherein when one filter is used, the filter has a pore diameter of 5 nm or less, and when two or more filters are used, the filter having the smallest pore diameter among the filters has a pore diameter of 5 nm or less.

Citation Information

Patent Citations

  • Production method of resist composition

    JP2015049395A